Successful Treatment of Giant Intracranial Aneurysm Using Flow-Diverter Device: First Experience in Nepal - Phuyal, Subash; Agrawal, Pooja; Lamsal, Ritesh; Neupane, Nirmal Prasad; Sedain, Gopal (Journal of Nepal Health Research Council, 2020)
Giant intracranial aneurysms are defined as aneurysms that measure over 25 mm in the greatest dimension. They are rare vascular lesions that preferentially involve regions with high-velocity blood flow, such as the cavernous and supraclinoid segments of the internal carotid artery, the middle cerebral artery, the vertebrobasilar region, and the basilar apex. The treatment of giant aneurysms is challenging and associated with high rates of morbidity and mortality. Flow-diverter devices have revolutionized their treatment in recent times. We report the successful management of two patients with giant cavernous internal carotid artery aneurysms using flow-diverter devices for the first time in Nepal. Keywords: Endovascular; flow-diverter devices; giant aneurysm